2020
DOI: 10.22270/jddt.v10i5.4422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phytocompounds and Chemical Elements Present In Selected Species of Seaweeds, to Sustain Future Quantitative Analysis for Bioactive Compounds

Abstract: Introduction: The specific physiological capacity of marine organisms, including seaweeds, to survive in extreme environmental conditions is associated to the production of secondary metabolites. Seaweeds are known as powerful source of a broad range of bioactive compounds. Objective: The aim of this study was to investigate the phytocompounds and chemical elements present in eight species of seaweeds which occur around Inhaca Island, Mozambique. Specifically, Halimeda cuneata, Pseudorhizoclonium africanum, Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Marine macroalgae produce both primary metabolites, including proteins, amino acids, polysaccharides, fatty acids, etc., and secondary metabolites, such as phenolic compounds, pigments, sterols, vitamins, and other bioactive components [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Moreover, various types of biological activities expressed by different phycocompounds, such as blood coagulation system, antilipidemic activity, immunomodulating effect, antiviral activity, anticancer activity, antimicrobial activity, antioxidant activity, and other significant activities [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Marine macroalgae produce both primary metabolites, including proteins, amino acids, polysaccharides, fatty acids, etc., and secondary metabolites, such as phenolic compounds, pigments, sterols, vitamins, and other bioactive components [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Moreover, various types of biological activities expressed by different phycocompounds, such as blood coagulation system, antilipidemic activity, immunomodulating effect, antiviral activity, anticancer activity, antimicrobial activity, antioxidant activity, and other significant activities [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical profiling of algal samples by advanced analytical techniques revealed the presence and relative amounts of different phytochemicals, many with important medicinal properties (e.g., antimicrobial, anti-inflammatory, antioxidant) [8,24]. Preliminary qualitative phytochemical analysis was carried out to identify the secondary metabolites such as alkaloids, flavonoids, terpenoids, steroids, tannins, phenols, quinones, glycosides, flavanones, flavonols, steroids, and saponins present in the alcoholic/aqueous extracts of marine algae [68][69][70]. The variation in the antimicrobial and antioxidant activities were due to various parameters at the time the algal samples were collected.…”
Section: Qualitative and Quantitative Aspects Of Algal-derived Biocompoundsmentioning
confidence: 99%
“…Other phytochemical screenings of different algal extracts were assessed using standard methods. An FeCl 3 test for tannins in methanolic extracts was assessed for brown seaweeds (i.e., Dictyota dichotoma and Sargassum wightii), green seaweeds (i.e., Cladophora glomerata, Ulva lactuca, and Ulva reticulata), and red seaweeds (i.e., Jania rubens, Corallina mediterranea, and Pterocladia capillacea), and the results revealed that tannins are common phytocompounds in seaweeds [68,70]. These algal species can be used as a drug for gonorrhea and as healing agents, and seem to exert anti-viral, anti-bacterial, and anti-ulcer activities [50,65].…”
Section: Qualitative and Quantitative Aspects Of Algal-derived Biocompoundsmentioning
confidence: 99%
See 2 more Smart Citations